2010
DOI: 10.2486/indhealth.ms1127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aerosol Emission and Hazard Evaluation of Electrical Discharge Machining (EDM) Process

Abstract: The safety and environmental aspects of a manufacturing process are important due to increased environmental regulations and life quality. In this paper, the concentration of aerosols in the breathing zone of the operator of Electrical Discharge Machining (EDM), a commonly used non traditional manufacturing process is presented. The pattern of aerosol emissions from this process with varying process parameters such as peak current, pulse duration, dielectric flushing pressure and the level of dielectric was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 10 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…However, health risks associated with EDM air pollution are not yet clearly understood (Andujar et al, 2014). Jose et al (2010) evaluated the aerosol exposure of DEDM and showed that the aerosol concentration at breathing zone of the operator was above the permissible limit for repairable particulates (5 mg/m 3 ). Unfortunately, no size fraction information was reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, health risks associated with EDM air pollution are not yet clearly understood (Andujar et al, 2014). Jose et al (2010) evaluated the aerosol exposure of DEDM and showed that the aerosol concentration at breathing zone of the operator was above the permissible limit for repairable particulates (5 mg/m 3 ). Unfortunately, no size fraction information was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24], environmental factors, such as aerosol concentration and dielectric consumption, require immediate attention.…”
Section: Mahdavinejad Andmentioning
confidence: 99%
“…To identify scenarios that would lead to the release of hazardous or flammable material into the atmosphere, consequently exposing workers to injury; D. To check the safety of the design; E. To improve the safety of an existing and/or modified facility. The process of performing HAZOP analysis [23] is based on three steps, as shown in Fig. 6.…”
Section: Hazard and Operability Analysismentioning
confidence: 99%
See 2 more Smart Citations